Group Agency and Overdetermination - Killoren, David (Ethical theory and moral practice, 2013)
A morally objectionable outcome can be overdetermined by the actions of multiple individual agents. In such cases, the outcome is the same regardless of what any individual does or does not do. (For a clear example of such a case, imagine the execution of an innocent person by a firing squad.) We argue that, in some of these types of cases, (a) there exists a group agent, a moral agent constituted by individual agents; (b) the group agent is guilty of violating a moral obligation; however, (c) none of the individual agents violate any of their moral obligations. We explicate and defend this view, and consider its applications to problems generated by anthropogenic climate change and electoral politics.